The effects of aging on the use of handheld augmented reality in a route planning task. (April 2018) - Peleg-Adler, Rinat; Lanir, Joel; Korman, Maria
Abstract: Technology may offer benefits for the older population in keeping their independence and connection to society. However, adopting new technologies, such as augmented reality (AR) by older adults may be difficult due to decline of cognitive and physical abilities as well as due to hostility and apprehension regarding the use of technology. In the current study, we compared performance of older and younger participants in a route planning task of public transportation, implemented using both a handheld see-through AR interface, and a standard non-AR application on a mobile phone. Faster task completion times but also higher error rates were associated with the use of the AR interface, regardless of the age of the participants. Older adults showed significantly slower performance compared to younger participants while using the AR application, however, error rates were not significantly different. No trial-to-trial learning was observed for the AR interface, indicating that the AR see-through technology is intuitive and easily adopted. Finally, elderly participants reported on average better user experience for the AR interface compared to younger participants, and preferred the AR over the non-AR application. Our findings highlight the potential of AR technology for older adults, as a possible aid tool to manage everyday tasks, such as navigation and planning. Highlights: A first empirical study that examines older adults' interaction with augmented reality. Older adults did not show relative performance deficits in using AR. No learning effect was found for AR for both older and younger participants. Older adults expressed a high level of appreciation and satisfaction from the AR application. Older adults preferred the AR application over a similar, non-AR application.